Emulsion gels and oil-filled aerogels as curcumin carriers: Nanostructural characterization of gastrointestinal digestion products. (1st September 2022) - Fontes-Candia, Cynthia; Martínez, Juan Carlos; López-Rubio, Amparo; Salvia-Trujillo, Laura; Martín-Belloso, Olga; Martínez-Sanz, Marta
Graphical abstract: Highlights: Agar and κ-carrageenan oil-filled gel-like structures are useful as curcumin carriers. Agar emulsion gels showed smaller and more homogeneously distributed oil droplets. After simulated gastrointestinal digestion bile salt lamellae/micelles were produced. Larger vesicles of partially digested oil were also generated. Polysaccharide type and physical state affect the digestion products' structures. Abstract: Agar and κ-carrageenan emulsion gels and oil-filled aerogels were investigated as curcumin carriers and their structure and mechanical properties, as well as their structural changes upon in vitro gastrointestinal digestion were characterized. Agar emulsion gels presented stiffer behaviour, with smaller and more homogeneous oil droplets (ϕ ∼ 12 µm) than those from κ-carrageenan (ϕ ∼ 243 µm). The structure of κ-carrageenan gels was characterized by the presence of rigid swollen linear chains, while agar produced more branched networks. After simulated gastrointestinal digestion bile salt lamellae/micelles (∼5 nm) and larger vesicles of partially digested oil (Rg  ∼ 20–50 nm) were the predominant structures, being their proportion dependent of the polysaccharide type and the physical state of the gel network. The presence of curcumin induced the formation of larger vesicles and limited the formation of mixed lamellae/micelles.